Studi Literatur Michelia champaca L. dan Potensinya Sebagai Antikanker dan Antimikroba - Widya Syahfitri; Zulia Ananda; Febry Rahmadhani Hasibuan (Jurnal Bioleuser, 2026)
Michelia champaca L. is a tropical plant widely utilized in Southeast Asian traditional medicine and recognized for its rich diversity of secondary metabolites. Recent phytochemical investigations have demonstrated that this species contains a broad spectrum of bioactive compounds, including flavonoid glycosides, aporphine alkaloids, phenolic compounds, terpenoids, and sesquiterpene lactones, all of which exhibit significant pharmacological potential. This review aims to systematically synthesize current scientific evidence on the phytochemistry and bioactivities of M. champaca, encompassing the isolation of bioactive constituents, characterization of metabolite profiles, and evaluation of antioxidant, antimicrobial, analgesic, cytotoxic, and anticancer activities. Available findings indicate that the leaves of M. champaca contain four newly identified flavonol diglycosides, along with numerous other flavonoid glycosides, which exhibit strong antioxidant activity as demonstrated by both chemical assays and intracellular reactive oxygen species (ROS) suppression. Aporphine alkaloids, particularly liriodenine isolated from the branches, have shown significant antiproliferative effects against A549 lung carcinoma and MDA-MB-231 breast cancer cell lines. Furthermore, antimicrobial activity is predominantly associated with the ethyl acetate and n-butanol fractions, which effectively inhibit the growth of Gram-positive and Gram-negative bacteria as well as pathogenic fungi. In addition, methanolic leaf extracts demonstrate notable analgesic and cytotoxic activities. Overall, this review underscores M. champaca as a promising source of bioactive metabolites with considerable potential for phytopharmaceutical development, particularly as natural antioxidants, antimicrobial agents, and anticancer therapeutics. The compiled evidence provides a robust scientific basis for future investigations into molecular mechanisms and the development of plant-based therapeutic formulations.